Invisible sovereign : imagining public opinion from the Revolution to Reconstruction - Schmeller, Mark G., 1967- (New studies in American intellectual and cultural history., 2016)
"Even today, with sophisticated surveys and computer-produced margins of error, we have trouble gauging the elusive voice we call 'public opinion,' but no one questions its importance in a democracy. In this insightful new study, Mark G. Schmeller sets out to recreate or approximate the nature of public opinion between independence and the aftermath of Civil War and also examine what leading Americans thought about it. Where could one detect it? How might attitudes toward it, in the abstract and concrete, have changed in this eventful period? 'As Americans contested the meaning of this essentially contestable concept,' Schmeller explains, 'they expanded and contracted the horizons of political possibility and renegotiated the terms of political legitimacy.' He argues that what began life as something close to exceptionally American republican thought (and in a sense unchanging) became something far more malleable and subject to manipulation by means of stump-speech rhetoric, partisan newspapers, trumpeting of the importance of the self in the nineteenth century, etc. Crossing into so many discrete fields of historical research, this project has much potential as a synthesizing meta-narrative"--